Differential role of internet-based targeted persuasive advertising versus mass advertising on firms with unique qualities in an anchoring perspective - Zhao Jiang; Wu Dan; Yue Lin-Jun (PLoS ONE, 2025)
A firm’s primary objective is to enhance its products’ perceived quality through persuasive advertising techniques, thereby influencing consumer purchase decisions. This research paper delves into the effects of different forms of persuasive advertising, specifically mass and Internet-based targeted persuasive advertising, on enhancing perceived product qualities within a competitive duopoly. The analysis takes into consideration a vertical differentiation model. The findings of this study demonstrate that both firms, each producing products with distinctive qualities, can augment the perceived quality of their offerings through the application of persuasive advertising strategies. Notably, a low-quality firm consistently adjusts its perceived quality to a fixed ratio of 4/7, leading to the anchoring effect on perceived quality. Meanwhile, it is observed that the firm manufacturing lower-quality products tend to rely more on mass persuasive advertising in comparison to its rival firm. Furthermore, targeted advertising through online channels proves to be advantageous in reaching a specific population that highly values the price-to-quality ratio. Specifically, a firm with superior quality that engages in Internet-based targeted persuasive advertising stands to gain more incredible benefits than its rival relying on mass persuasive advertising. These findings shed light on the distinct impacts of various persuasive advertising approaches on competitive firms with unique qualities. Essentially, it underscores the significance of strategic advertising decisions in effectively influencing consumers’ perceived product qualities and gaining a competitive edge in the market.